Professional Development Programs and Teachers’ Self-Efficacy: A Correlation - Khairunnisa Fitri (Institut Agama Islam Negeri Palopo, 2023)
This study aims at investigating the correlation between professional development programs and teachers’ self-efficacy. The professional development program is one of the ways that is believed can enhance teachers’ self-efficacy which is directly related to teaching skills and practice in the classroom. The data that is related to Professional Development Programs and teachers’ self-efficacy was obtained using PDP and TSES questionnaires. Thirty English teachers from Blangkejeren district were involved. The data then were analyzed by using Product Moment Correlation to obtain the correlation between the variables and the degree of the correlation. The findings indicated that a professional development program correlated positively with teachers’ self-efficacy (p-value= 0,380 < 0,05). Furthermore, the degree of the correlation is 0, 381 which indicated a weak correlation but positive. The findings implied that Professional Development Program is not the only element that might impact teachers' sense of efficacy. The implication of the result of the professional development program and teachers’ self-efficacy was discussed.